Health Diplomacy as an Instrument of Indonesian Foreign Policy - Marianne Delanova (Journal Of Global Strategic Studies, 2021)
Indonesia’s foreign policy is dynamic, especially in the COVID-19 Pandemic Era. When Indonesia experienced an increase in COVID-19 cases, it identified it as a foreign policy issue requiring attention. It focused on promoting national health resilience in health care as one way to protect the Indonesian state during the COVID-19 pandemic. The purpose of this paper is to explain and analyze Indonesia’s health diplomacy as an instrument of Indonesia’s foreign policy in the era of the COVID-19 pandemic. It argues that, so far, the results of Indonesia’s health-focused approach are good and in line with Indonesia’s national interests. Indonesia’s active role and involvement in international forums has a diplomatic purpose but has also helped other countries. This indicates that the health diplomacy carried out by Indonesia has had a major impact on regional and global stability. In addition, Indonesia’s health diplomacy has resulted in it receiving assistance in the form of medical devices and vaccines provided by other countries for handling COVID-19 in Indonesia. Indonesia was also the driving force in the initiation in the 75th United Nations General Assembly of measures giving voice to the availability of medical devices and vaccine equality for all countries in the world.